E-Discovery : (Cengage Learning, 2014)
Essential for anyone who works with technology in the field, E-DISCOVERY is a "hands-on, how-to" training guide that provides readers with comprehensive coverage of the technology used in e-discovery in civil and criminal cases. From discovery identification to collection, processing, review, production, and trial presentation, this practical text covers everything the reader needs to know about e-discovery, including the Federal Rules of Civil Procedure, Federal Rules of Criminal Procedure, and Federal Rules of Evidence. Throughout the text, the reader will have the opportunity to work with e-discovery tools such as Discovery Attender, computer forensics tools such as AccessData's Forensics ToolKit, as well as popular processing and review platforms such as iConect, Concordance, and iPro. An interactive courtroom tutorial and use of Trial Director are included to complete the litigation cycle. Multiple tools are discussed for each phase, giving the reader a good selection of potential resources for each task. Finally , real-life examples are woven throughout the text, revealing little talked-about potential pitfalls, as well as best practice and cost management suggestions.